2000
DOI: 10.1021/cm9907099
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Conducting Polymers:  Oxygen Reduction by a Polythiophene−Cobalt Salen Hybrid

Abstract: Polythiophene−transition metal hybrid materials based on cobalt salen have been prepared and shown to catalyze the reduction of O2. The conjugated nature of the polymer backbone allows for facile electron transfer from the polymer surface to the active metal centers to affect this reduction. Rotating ring−disk measurements show only minute amounts of H2O2, indicating a selective reduction of O2 to H2O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 24 publications
1
65
0
Order By: Relevance
“…To this end, a transition metal-containing polythiophene, when immobilised on an electrode, has proven effective in catalysing the four electron reduction of dioxygen to water. [163] It was suggested that the high efficiency was due to the well redox-matched system enabling rapid transport of electrons to the metal centre.…”
Section: Catalysis and Electrocatalysismentioning
confidence: 99%
“…To this end, a transition metal-containing polythiophene, when immobilised on an electrode, has proven effective in catalysing the four electron reduction of dioxygen to water. [163] It was suggested that the high efficiency was due to the well redox-matched system enabling rapid transport of electrons to the metal centre.…”
Section: Catalysis and Electrocatalysismentioning
confidence: 99%
“…[10] Therefore the pta molecule could be an excellent ligand from which to obtain water-soluble Ru-Au polymers which could have interesting and useful properties for a variety of applications such as magnetism, [11] nonlinear optics, [12] electrocatalysis, [13] photocatalysis, [14] photovoltaic, [15] template formation of ordered networks, [16] advanced electrode materials, [17] and conjugated coordination polymers.…”
mentioning
confidence: 99%
“…To the best of our knowledge, reactivity of the -diketones containing thienyl moieties toward diamines has been scarcely reported in the literature [15]. The incorporation of thienyl units in the structure of a compound not only opens up opportunities to the formation of polymeric [16,17] and metallopolymeric materials [18,19], either through chemical or electrochemical oxidation of the thienyl units [20][21][22], but also to the development of new drugs [4].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%